Galp energia: Financial statements analysis and projections for the future - Vitorino, Pedro Trigueiros Sampaio Ferreira (2014)
The oil and natural gas sectors have been knowing in a recent past deep alterations in its operational activity due to various factors – exogenous and endogenous. This project provides a general overview of a Portuguese oil and natural gas company, analyzing the past 6 years and producing a projection for the future 4 years. A Financial Statements Analysis will be performed. Financial information of the company will be analyzed – through the use of the appropriate ratios - during the period of 2006 to 2010 in order to provide a picture of the determinant oil and natural gas industry indicators. An analysis on the evolution of these indicators will be conducted, resulting on a pattern of behavior on operational and financial issues to be regarded. Given that pattern, a projection for the period of 2010 to 2014 will take place regarding the main operational and financial conclusions from the Financial Statements Analysis conducted before. Conclusions on this projects will be asserted regarding operational and financial main issues mentioned before, but also a view of integration of oil and gas sectors on the new economic world order concerning the emerging economies potential to the sector.